Previously Complicated Nuss Procedure Does Not Preclude Blind Removal of the Bar - BOSTANCI, KORKUT; ERMERAK, NEZİH ONUR; LAÇİN, TUNÇ (GEORG THIEME VERLAG KG, 2016)
Background Nuss procedure has become the procedure of choice for well-selected patients with pectus excavatum. Perioperative complications may pose difficulty during the subsequent bar removal due to adhesions and tissue plane disruptions during the initial surgery and repair. This report describes bar removal experience in patients whose Nuss procedures were complicated by cardiac injury, pericardial breach, and lung parenchyma/diaphragm injury during the initial procedure. Methods A total of 529 patients who underwent Nuss procedure between 2007 and 2014 were recorded in a prospective database. Twenty patients with complications (cardiac injury [n = 1], pericardial breach [n = 3], and lung parenchyma/diaphragm injury [n = 16]) were identified. All bars were removed via subcutaneous tissue dissection, without intrathoracic visualization. Results Average duration of bars was 36 months (+/- 16 months). All bar removal procedures were completed without any need for extra interventions with negligible blood loss. Eighteen patients were able to be discharged within 2 postoperative days. Conclusion Blind bar removal in patients with previously complicated Nuss procedure seems safe and no other interventions (videothoracoscopy, subxiphoid incision, etc.) during bar removal seem to be necessary.
Keywords: pectus excavatum; Nuss procedure; bar removal; PECTUS BAR